GESTIÓN DEL TALENTO HUMANO EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO DE LA CIUDAD DE BABAHOYO - Onofre Cardenas, manuel Adolfo (2019)
he management of human talent is important in any company, this seeks to improve the potential of employees in their jobs, is a key point to perform an analysis of the problems within the Autonomous Decentralized Government of the city of Babahoyo, through the observation where a highly competitive environment has been generated that is constantly growing, the vision of the search for an efficient human staff is vital for the operations that face obstacles when there are errors, this strengthens and promotes a more efficient organization besides ensuring that the various cooperation activities run smoothly.